Hubungan Marketing Public Relations dengan Brand Awareness - Indriani Putri Amadea; Riza Hernawati (Jurnal Riset Public Relations, 2023)
Abstract: Pijar Mahir is an online certified training platform that is one of the partners of Kartu Prakerja along with seven other partners. Given the covid-19 pandemic conditions that we are facing, all promotions and marketing carried out must be changed to be all online by using social media as a medium with the aim of achieving brand awareness on the Pijar Mahir platform. This study aims to obtain data and information that provides an overview of how @pijarmahir.id's Instagram digital marketing strategy is related to the brand awareness of Instagram followers @pijarmahir.id using the Stimulus Theory of Response Organisms (SOR) with the help of the three ways strategy model of public relations marketing with the Brand Awareness Level . In this study, researchers used correlational quantitative methods with a population of 30,069 people. From this population, researchers used the Yamane formula to find out the sample results and there were sample results of 395 people as respondents using a simple random sampling technique. Data collection is carried out using an online questionnaire through google form, after the data is collected according to the target data will be processed using the IBM SPSS application and analyzed using The Spearman Rank. The results of this study show that there is a significant relationship between the marketing public relations used by @pijarmahir.id and the brand awareness of @pijarmahir.id's Instagram followers. Abstrak: Pijar Mahir adalah platform pelatihan bersertifikat online yang menjadi salah satu mitra Kartu Prakerja bersama dengan tujuh mitra lainnya. Mengingat kondisi pandemi COVID-19 yang sedang kita hadapi, seluruh promosi serta marketing yang dilakukan harus dirubah konsepnya menjadi serba online dengan menggunakan media sosial sebagai medianya dengan tujuan mencapai kesadaran merk (Brand Awareness) pada platform Pijar Mahir . Penelitian ini memiliki tujuan untuk memperoleh data dan informasi yang memberikan gambaran tentang bagaimana hubungan strategi digital marketing instagram @pijarmahir.id dengan brand awareness pengikut Instagram @pijarmahir.id dengan menggunakan Teori Stimulus Organisme Respons (SOR) dengan dibantu model three ways strategy marketing public relations dengan Tingkatan Brand Awareness. Dalam penelitian ini, peneliti menggunakan metode kuantitatif korelasional dengan populasi sebanyak 30.069 orang. Dari populasi tersebut peneliti menggunakan rumus Yamane untuk mengetahui hasil sampelnya dan terdapat hasil sampel sebanyak 395 orang sebagai responden dengan menggunakan teknik simple random sampling. Pengumpulan data dilakukan dengan menggunakan kuisioner online melalui google form, setelah data terkumpul sesuai target data akan diolah dengan menggunakan aplikasi IBM SPSS dan dianalisis dengan menggunakan Rank Spearman. Hasil dari penelitian ini menunjukan bahwa adanya hubungan yang signifikan antara marketing public relations yang digunakan oleh @pijarmahir.id dengan brand awareness pengikut instagram @pijarmahir.id.